(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of knowledge and practices regarding food safety among food service business owners under the management of Phuoc Long regional Medical Center, Ca Mau province, in 2025. Methods: A cross-sectional study was conducted among food service business owners in Phuoc Long commune, Ca Mau province, in 2025. Results: The study results showed that 58.7% of food service business owners had correct knowledge about food safety, while only 29.3% had correct food safety practices. The study also found a statistically significant association between knowledge and practice (OR = 3.61; 95% CI: 2.19-5.96; p < 0.001), indicating that those with correct knowledge were more likely to have correct practices than those with incorrect knowledge. Conclusion: The study indicates that compliance with food safety among food service business owners remains limited, particularly in food processing and storage practices. Knowledge plays an important role in improving food safety practices. Therefore, strengthening communication, training, and supervision is necessary to improve awareness and promote safe food practices in food service establishments.